Internationalization of Indonesian culinary in learning Indonesian as a foreign language (BIPA): A case of American students - Saddhono, Kundharu Saddhono; Istanti, Wati; Kusmiatun, Ari; Kusumaningsih, Dewi; Sukmono, Indriyo K.; Saputra, Aldi Dwi (Research Journal in Advanced Humanities, 2024)
Increased interest in the Indonesian language and culture among foreign students in the United States has drawn attention to the internationalization of Indonesian cuisine as an integral part of Indonesian Language for Foreign Speakers (BIPA) education. This research aims to explore the potential for the internationalization of the Indonesian language through a scientific-thematic approach by integrating Javanese culinary tourism into the Indonesian language teaching materials for international students (BIPA) in the United States. The study identifies how a learning method focused on Javanese culinary tourism can enhance international students’ understanding and proficiency in the Indonesian language, as well as how interactions with culinary culture help them comprehend the social, cultural, and historical values of Indonesia. This research employs a qualitative research method with a case study approach. Data is obtained through surveys and interviews with BIPA students studying Indonesian through culinary means, as well as instructors and program administrators at Yale University, United States. The data obtained from this research include expert validation data on the instrument’s feasibility, expert validation data on the effectiveness of the developed teaching materials, and practicality data of teaching materials in the form of practicality scores filled out by BIPA students and teachers. The results of this study indicate that, in teaching nasi goreng as a BIPA teaching material, it is crucial to ensure that the approach used is relevant, enjoyable, and tailored to the needs and proficiency levels of the students. As mentioned earlier, the integration of Javanese culinary tourism into Indonesian language teaching materials for foreign speakers using a scientific-thematic approach is an effective way to introduce nasi goreng and Indonesian culture to BIPA students in the United States or elsewhere.